B cell receptor signatures associated with strong and poor SARS-CoV-2 vaccine responses. Issue 1 (31st December 2022) - Lin, Ke; Zhou, Yawen; Ai, Jingwen; Wang, Yan A.; Zhang, Senxin; Qiu, Chao; Lian, Chaoyang; Gao, Bo; Liu, Tingting; Wang, Hongyu; Zhang, Haocheng; Zhang, Yi; et al.
ABSTRACT: Breakthrough infection of SARS-CoV-2 is a serious challenge, as increased infections were documented in fully-vaccinated individuals. Recipients with poor antibody response are highly vulnerable to reinfection, whereas those with strong antibody responses achieve sterilizing immunity. Thus far, biomarkers associated with levels of vaccine-elicited antibody response are still lacking. Here, we studied the antibody response of age- and gender-controlled healthy cohort, who received inactivated SARS-CoV-2 vaccines and profiled the B cell receptor repertoires in longitudinally consecutive samples. Upon vaccination, all vaccinated individuals displayed a convergent antibody response with shared common antibody clones and public neutralizing antibodies. Strikingly, poor vaccine-responders are distinguishable from strong vaccine-responders by a biased V-usage before vaccination and IgG to IgM mRNA ratio. These findings reveal molecular signatures associated with the different levels of vaccine-induced antibody response, which could be further developed into biomarkers for the design of vaccination strategies.